The associations of psychopathology and metabolic parameters with serum bilirubin levels in patients with acute-episode and drug-free schizophrenia: a 5-year retrospective study using an electronic medical record system - Yinghan Tian; Cheng Yang; Lewei Liu; Xin Zhao; Haojie Fan; Lei Xia; Huanzhong Liu (BMC Psychiatry, 2024)
Abstract Background The oxidative system plays an important role in the pathogenesis of schizophrenia. Inconsistent associations were found between hyperbilirubinemia and psychopathology as well as glycolipid metabolism in patients with schizophrenia at different episodes. This current study aimed to examine these associations in patients with acute-episode and drug-free (AEDF) schizophrenia. Methods This is a retrospective study using 5 years of data from May 2017 to May 2022 extracted from the electronic medical record system of Chaohu Hospital of Anhui Medical University. Healthy controls (HCs) from the local medical screening center during the same period were also included. Participants’ data of the bilirubin levels [total bilirubin (TB), conjugated bilirubin (CB), unconjugated bilirubin (UCB)], glycolipid metabolic parameters and the score of the Brief Psychiatric Rating Scale (BPRS) were collected. Results A total of 1468 case records were identified through the initial search. After screening, 89 AEDF patients and 100 HCs were included. Compared with HCs, patients had a higher CB level, and lower levels of glycolipid metabolic parameters excluding high density lipoprotein-cholesterol (HDL-C) (all P < 0.001). Binary logistic regression analyses revealed that high bilirubin levels in the patients were independently associated with higher total and resistance subscale scores of BPRS, a higher HDL-C level, and lower total cholesterol and triglyceride levels (all P < 0.05). Conclusion Bilirubin levels are elevated in patients with AEDF schizophrenia. Patients with high bilirubin levels have more severe psychopathology and relatively optimized glycolipid metabolism. In clinical practice, regular monitoring of bilirubin levels in this patient population should be carried out.